PROBLEMS OF THE LAND TAX IN THE REPUBLIC BURYATIA - Anna A. Kokorina; Darya A. Pavlutsky (Статистика и экономика, 2016)
Article retractedThe article discusses the history of the development land tax, since ancient times to the present, considered the signicance of the land tax in the formation of the local budget. According to the results of the research we can say that the land tax has a special place in the tax system of the Russian Federation. On the «Ulan-Ude city» example MO City District found that the land tax is a relatively low share of the local budget, however, the land tax has been an important source of formation of the budget settlement. In modern Russia, the land tax is seen as an effective mechanism for land management